The structure design and cutting performance research about the groove of the indexable inserts for machining stainless steel - Rongchuan Lin; Yuanyou Li; Renqi Xie; Jiahao Meng; Shasha Wei; Qingmin Huang; Yuhui Zhou (Materials Research Express, 2023)
Stainless steel is a notoriously difficult-to-machine material, with challenges such as hard-to-break chips and severe tool wear. To address these issues, a finishing indexable insert has been designed and developed specifically for stainless steel. This tool, named HMF, was compared to commercial tools (NF4, BF) in terms of its curved groove structure and cutting performance using SEM (scanning electron microscope Sigma500), 3D scanning (KEYENCE-VR 5000) and a profiler (Mitutoyo C-200). The HMF tool utilizes a curved edge with a curved chip breaker, and a chip-breaking bump on the tool nose. The groove parameters of the HMF insert are as follows: cutting edge angle of 12°, chip breaker groove width of 1.89 mm, back wall height of 0.095 mm, and anti-chip angle of 4°49’. 3D scanning of the chip break site reveals that the HMF chip break has a higher bump and a more pronounced chip rolling effect. HMF tool chip-breaking experiments show that it has ideal chip-breaking performance in the finishing range of ap = 0.6–1.0 mm, and f = 0.1–0.25 mm r ^−1 . Chip analysis shows that the HMF chip curl frequency increases and the chip curl is tighter as the feed rate increases, and the curl radius gradually decreases when the feed rate is greater than 0.15 mm r ^−1 . The results of the wear performance study are as follows: all three tools show rake face crater wear when cutting stainless steel. A small amount of built-up edge appears on the HMF cutting edge. The wear life of HMF is close to NF4 and better than BF; the wear of BF is faster in the later stages of wear.